Study of the Relationship between Communication Competence and Heart Rate Variability among International Postgraduate Students of a Malaysian Public University - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (Universiti Malaysia Pahang, 2016)
Communication competence is among the main skills that enable individuals to conduct fruitful interactions with different people. This study was carried out to examine the relationship between communication competence and heart rate variability (HRV) among individuals from different nationalities. The quantitative method was used to conduct this study. This study had two data collection procedures which were the quantitative survey and HRV data set. The participants of this study were 128 postgraduate students of a Malaysian public university. Based on their agreements, 40 of them were participated in the HRV data collection procedure of this study. Based on the results from this study, the levels of communication competence and heart rate variability of the participants had close relationship, and individuals with good levels of communication competence were good in heart rate variability and vice versa. Based on the results, their good scores of heart rate variability as an important internal factor helped the participants to increase the levels of their communication competence and their good levels of communication competence helped them to have more successful interactions with their peers. The results from this study may be helpful for future researchers to focus on these issues and also for university students to pay attention on their daily communication as an important factor for their personal and university related lives.